Ansätze der Berufslaufbahnforschung in dynamischen Arbeitsumwelten. - Volmer, Judith; Spurk, Daniel; Abele-Brehm, Andrea (Handbuch Berufsforschung, 2013)
Es wird informiert über die Forschung zur beruflichen Laufbahnentwicklung. Nach einleitenden terminologischen Klärungen wird auf Modelle der beruflichen Laufbahnentwicklung und auf den Stellenwert der Selbstregulation im Kontext der beruflichen Entwicklung eingegangen. Es wird betont, dass J. L. Hollands Theorie zur Berufswahl und das dazu gehörende (eher statische) Hexagonmodell der Interessen (trotz sich dynamisch entwickelnder Arbeitsumwelten) eine gute Möglichkeit zur ersten beruflichen Orientierung oder aber zu einer späteren Neuorientierung während des Berufsverlaufs bieten. Insgesamt aber entsprechen statische und an einem starren Muster orientierte entwicklungsbezogene Theorien nicht mehr den heutigen Rahmenbedingungen des Arbeitslebens. Erwerbstätige Personen und Laufbahnberater sind mit dynamischen Arbeitsumwelten konfrontiert, die Selbststeuerungskompetenzen und "employability" als zentrale Erfolgsfaktoren verlangen. Neben der klaren, effizienten Zielimplementierung und -verfolgung sind dabei flexibles und adaptives Reagieren auf Veränderungen im Berufsleben sowie Eigeninitiative bei der Initiierung entsprechender Veränderungen wichtig. Eine Aufgabe zukünftiger Forschung wird darin gesehen, unterschiedliche Laufbahnentwicklungskonzepte auf ihre Gültigkeit in unterschiedlichen beruflichen Kontexten hin zu überprüfen.
Keywords: Berufliche Entwicklung; Selbstregulation; Arbeitstauglichkeit; Berufswahl; Berufliche Interessen; Entwicklung im Erwachsenenalter; Berufe; Ziele; Modelle

Berufliche Exploration - Ebner, Katharina; Spurk, Daniel (Lexikon der Berufsbildung, 2016)

Calling and Burnout: Integrating Career Research with Occupational Health Psychology - Hagmaier-Göttle, Tamara; Volmer, Judith; Spurk, Daniel (Psychology of burnout : new research, 2013)
People are increasingly in search for meaning in their work and private life. They want to increase their self-awareness and reach personal fulfillment. People who are not able to cope with life's challenges often suffer from burnout, anxiety and depression. Consequently, the construct of calling becomes more and more important in the occupational context because of its positive consequences regarding numerous work (e.g. organizational commitment) and non-work-related outcomes (e.g. depression, life satisfaction) for individuals as well as for organizations. Building on first promising findings, the aim of the following chapter is to investigate the association of experiencing a calling in one's job and burnout (here defined as psychological phenomenon of prolonged exhaustion and disengagement at work, cf., Maslach, Schaufeli, & Leiter, 2001). Our findings suggest that experiencing one's work as a calling is negatively related to burnout. Especially with regard to the sub-dimension of disengagement, experiencing a calling turned out to be a protective factor. Further, the burnout sub-dimension of disengagement mediated the relationship between the experience of a calling and job satisfaction. Implications for further research and health-related preventive strategies are discussed.
Keywords: Beruflicher Stress; Organisationsverbundenheit; Gesundheit am Arbeitsplatz; Angst; Depressive Stimmung; Lebenszufriedenheit; Arbeitszufriedenheit; Protektive Faktoren

Career Decision Making: Relationships with Constructs Related to Employability and Initial Validation of the German Career Decision Making Profile - Ebner, Katharina; Thiele, Lisa; Kauffeld, Simone; Spurk, Daniel (17th Congress of the European Association of Work and Organizational Psychology, 2015)

Career stagnation: Underlying dilemmas and solutions in contemporary work environments. - Abele, Andrea E.; Volmer, Judith; Spurk, Daniel (Work and quality of life: ethical practices in organizations. International handbooks of quality-of-life., 2012)
Most people experience phases in which they do not move ahead or in which they feel that they are not making career progress. These phases can be factual, for example, when someone does not get promoted; they can also be a subjective interpretation, for example, when a person has unrealistic career goals, or a generally pessimistic worldview. In this chapter, we are concerned with career stagnation as the involuntary—at least temporary—end of one's career development. Career stagnation has a negative impact on a person's quality of life. This negative impact will be the stronger the longer this career stagnation is experienced and the more a person feels unable to overcome it. Career stagnation will become a dilemma when an individual is not able to cope with it and/or if every means of dealing with career stagnation has both desired and undesired consequences. This chapter deals with dilemmas associated with career stagnation and thereby focuses on objective (e.g., promotion stagnation) and subjective (e.g., dissatisfaction) aspects of career stagnation. In the first section of the chapter, specific person-level and interpersonal-level dilemmas (self-efficacy-related, goal-related, attitude-related, dual-career-related) are identified and possible influences on objective and subjective career stagnation will be addressed. In the second section of the chapter, specific organization-level dilemmas (lack of support, bullying/mobbing, stereotypes/discrimination) are identified and again influences on objective and subjective career stagnation are addressed. In the third section of the chapter, interventions to overcome these dilemmas will be presented (e.g., self-efficacy and self-management trainings, career counseling, mentoring, anti-mobbing/anti-bullying strategies, recruitment strategies for dual-career couples, and antidiscrimination strategies). Throughout this chapter, we will refer to unethical behavior as the injury of the employees' rights of balance, respect, responsibility, autonomy, participation, justice, and voice. More specifically, we will identify topics in which these rights may be ignored easily by the employer and/or the employee, and we will give recommendations on how to deal with these potentially unethical workplace situations. Further topics that may be relevant in regard to career stagnation such as job insecurity, unemployment, or dead-end jobs will not be discussed as they are beyond the scope of this chapter. (PsycINFO Database Record (c) 2012 APA, all rights reserved)
Keywords: career stagnation; work environments; career development; quality of life; quality of work life; job dissatisfaction; ethical behavior

Does Career Success Make You Happy? The Mediating Role of Multiple Subjective Success Evaluations. - Abele, Andrea E.; Hagmaier-Göttle, Tamara; Spurk, Daniel (Journal of Happiness Studies, 2015)
We hypothesize that career success assessed as objective career achievements (income and responsibility status) has an indirect positive association with life satisfaction that is channeled through multiple subjective success evaluations. These are based on (a) social comparisons (comparison with others, other-referent success evaluation) and (b) individual standards (satisfaction with career achievements, self-referent success evaluations). We tested our reasoning in a 2-year prospective study with N = 990 professionals. Controlling for gender, family status, and workload, the results of two mediation models that draw on all information from two measurement points supported our reasoning. We found indirect positive associations between career success and life satisfaction (H1) channeled through both other-referent (H2) and self-referent (H3) subjective success evaluation. In both mediation models, we found partial mediation, and the remaining direct path from career success to life satisfaction was negative. We conclude that career success has mixed effects on a person’s life satisfaction: The net effect of positive indirect and negative direct effects is positive, but not large. We discuss the significance of these findings for theorizing about the influence of the work domain on life satisfaction as well as for conceptual issues in the analysis of mediators and moderators of the career success life satisfaction association. (PsycINFO Database Record (c) 2015 APA, all rights reserved)

How do objective and subjective career success interrelate over time? - Abele, Andrea E.; Spurk, Daniel (Journal of Occupational and Organizational Psychology, 2009)
The present research is concerned with the direction of influence between objective and subjective career success. We conducted a prospective longitudinal study with five waves of measurement that covered a time span of 10 years. Participants were professionals working in different occupational fields (N = 1,336). We modelled the changes in objective success (income, hierarchical position), in other-referent subjective success (subjective success as compared to a reference group), and in self-referent subjective success (job satisfaction) by means of latent growth curve analysis. Objective success influenced both the initial level and the growth of other-referent subjective success, but it had no influence on job satisfaction. Most importantly, both measures of subjective success and both their initial levels and their changes had strong influences on the growth of objective success. We conclude that the ‘objective success influences subjective success’ relationship is smaller than might be expected, whereas the ‘subjective success influences objective success’ relationship is larger than might be expected. (PsycINFO Database Record (c) 2012 APA, all rights reserved)
Keywords: objective and subjective career success; time; income; hierarchical position; other-referent subjective success; self-referent subjective success; job satisfaction

Laufbahnberatung - Ebner, Katharina; Spurk, Daniel (Lexikon der Berufsbildung, 2016)

Leader-member exchange (LMX), job autonomy, and creative work involvement - Niessen, Cornelia; Spurk, Daniel; Volmer, Judith (The Leadership Quarterly, 2012)
Researchers have claimed that high quality of supervisor-employee relationships (i.e., leader-member exchange; LMX) fosters creativity at work. Moreover, researchers have acknowledged that this relationship is not clear-cut but rather complex. The present study focused on the moderating role of job autonomy in the LMX-creative work involvement relationship. Longitudinal field survey data (. N=. 144) collected in a high-technology firm revealed a positive association between LMX and creative work involvement and confirmed our assumptions on the moderating role of job autonomy. The positive relationship between LMX and creative work involvement was stronger when employees experienced greater job autonomy. Our findings point to the importance of considering the interplay of both, the leader-member relationship and job design issues for increasing employees' creative work involvement. © 2011 Elsevier Inc.

Leading for creativity - Volmer, Judith; Spurk, Daniel; Niessen, Cornelia (26st Annual SIOP Conference, 2011)

Longitudinal Effects of Career Adaptability on Job and Career Insecurity via two Types of Perceived Marketability - Spurk, Daniel; Meinecke, Annika; Kauffeld, Simone; Ebner, Katharina (17th Congress of the European Association of Work and Organizational Psychology, 2015)

Messung von Karriereerfolg. - Abele-Brehm, Andrea; Spurk, Daniel (Management-Diagnostik, 2013)
Keywords: Führungskräfte; Beruflicher Erfolg; Berufliche Entwicklung; Evaluationskriterien; Berufliche Leistung

Prognose von Berufserfolg: Überblick und aktuelle Trends. - Spurk, Daniel; Volmer, Judith; Abele-Brehm, Andrea (Handbuch Berufsforschung, 2013)
Es wird informiert über die Forschung zur Prognose von Berufserfolg. Zunächst wird auf das Konzept des Berufserfolgs und dessen Korrelate eingegangen. Berufserfolg wird als Ergebnis von Wettkampf oder Förderung und übergeordneten Prognosekategorien (Humankapital, organisationale Förderungsmaßnahmen, soziodemographische Variablen, stabile individuelle Unterschiede) thematisiert. Bei der Darstellung aktueller Entwicklungen wird unter anderem darauf hingewiesen, dass in jüngster Vergangenheit selbstregulatorische Ansätze mit Konzepten wie Selbstwirksamkeit oder Zielen verstärkt berücksichtigt werden und dass Mobilitätstheorien im Sinne von tatsächlicher geographischer und organisationaler Mobilität sowie dazugehörige psychologische Konstrukte wie "neue" Karriereeinstellung im Kontext der Prognose von Berufserfolg an Bedeutung gewinnen. Abschließend werden zentrale Forschungsergebnisse zusammengefasst und aktuelle Trends benannt. Dabei wird unter anderem hervorgehoben, dass selbstregulatorische Kompetenzen für heutige (oft nicht gradlinig verlaufende) Berufsprozesse besonders wichtig sind, dass das Setzen von inhaltlich berufsbezogenen persönlichen Zielen und das Vertrauen in die eigenen beruflichen Fähigkeiten und die regelmäßige Adjustierung von verfolgten Zielen für erwerbstätige Personen entscheidend sind, um langfristig beschäftigungsfähig zu bleiben und erfolgreich zu sein. Weitere Forschung über die Veränderbarkeit selbstregulativer Kompetenzen (etwa berufliche Selbstwirksamkeit) wird für wichtig erachtet, da so gezielt Trainings- bzw. Interventionsmaßnahmen in der Personalarbeit und Laufbahnberatung entwickelt, angeboten und durchgeführt werden können. Es wird die Ansicht vertreten, dass aufgrund globalisierter und dynamischer Arbeitswelten, die sich zudem interkulturell und bereichsspezifisch unterscheiden, selbstregulative Fähigkeiten zukünftig noch wichtiger werden.
Keywords: Berufserfolgsprognose; Beruflicher Erfolg; Psychologische Theorien; Selbstregulation; Berufsberatung; Arbeitnehmermerkmale; Zielsetzung; Individuelle Unterschiede

Reciprocal relationships between leader-member exchange (LMX) and job satisfaction: A cross-lagged analysis - Volmer, Judith; Niessen, Cornelia; Linz, Alexandra; Spurk, Daniel; Abele, Andrea E. (Applied Psychology, 2011)
While previous research has mainly emphasised the importance of leader-member exchange (LMX) to job satisfaction, there is a lack of research on reciprocal relationships between job satisfaction and LMX. In this study, we not only suggest that good LMX increases job satisfaction, but that job satisfaction can also enhance high-quality supervisor-employee relationships. A full cross-lagged panel analysis was used to test reciprocal relationships between LMX and job satisfaction. Employees (N= 279) of a large information technology company filled out questionnaires at two times, with a time lag of 3 months. In line with our predictions, findings revealed a positive relationship between LMX and job satisfaction both at Time 1 and Time 2. Moreover, LMX at Time 1 predicted the increase of job satisfaction at Time 2, and job satisfaction at Time 1 predicted the increase of LMX at Time 2. The results demonstrate the need to consider reciprocal relationships between job satisfaction and LMX when explaining employees' workplace outcomes. Our findings are discussed in terms of positive psychology theory. © 2011 The Authors. Applied Psychology: An International Review © 2011 International Association of Applied Psychology.

Relations of within-person incongruities with life satisfaction and self-efficacy: The moderating role of career coaching - Ebner, Katharina; Spurk, Daniel; Schulte, Eva-Maria; Kauffeld, Simone (International Conference for Well-Being and Performance, 2014)

Synchronous and time-lagged effects between occupational self-efficacy and objective and subjective career success: Findings from a four-wave and 9-year longitudinal study. - Spurk, Daniel; Abele, Andrea E. (Journal of Vocational Behavior, 2014)
We integrated research on the dimensionality of career success into social-cognitive career theory and explored the positive feedback loop between occupational self-efficacy and objective and subjective career success over time (self-efficacy → objective success → subjective success → self-efficacy). Furthermore, we theoretically accounted for synchronous and time-lagged effects, as well as indirect reciprocity between the variables. We tested the proposed model by means of longitudinal structural equation modeling in a 9-year four-wave panel design, by applying a model comparison approach and indirect effect analyses (N = 608 professionals). The findings supported the proposed positive feedback loop between occupational self-efficacy and career success. Supporting our time-based reasoning, the findings showed that unfolding effects between occupational self-efficacy and objective career success take more time (i.e., time-lagged or over time) than unfolding effects between objective and subjective career success, as well as between subjective career success and occupational self-efficacy (i.e., synchronous or concurrently). Indirect effects of past on future occupational self-efficacy via objective and subjective career success were significant, providing support for an indirect reciprocity model. Results are discussed with respect to extensions of social-cognitive career theory and occupational self-efficacy development over time. (PsycINFO Database Record (c) 2014 APA, all rights reserved)
Keywords: Selbstwirksamkeit; Beruflicher Erfolg; Arbeitnehmereinstellungen; Selbsteinschätzung; Berufliche Entwicklung; Erwachsenenalter; Deutschland

The Career Satisfaction Scale in Context: A Test for Measurement Invariance across Four Occupational Groups. - Spurk, Daniel; Abele, Andrea E.; Volmer, Judith (Journal of Career Assessment, 2015)
Analyzed the influence of occupational context on the conceptualization of career satisfaction as measured by the Career Satisfaction Scale (CSS). In a sample of 729 highly educated professionals (mean age 42 years), a cross-occupational (i.e., physicians, economists, engineers, and teachers) measurement invariance analysis was performed. Results show that the CSS was conceptualized according to occupational group membership; that is, four of the five items of the scale showed measurement variance. More specifically, the relative importance, the response biases, and the reliabilities associated with different career satisfaction content domains measured by the CSS (i.e., achieved success, overall career goals, goals for advancement, goals for income, and goals for development of new skills) varied by occupational context. However, results of a comparison between manifest and latent mean differences between the occupational groups revealed that the observed measurement variance did not affect the estimation of mean differences. It is concluded that occupational groups vary in context, and that occupational context is an important variable to be considered when researching career success and subjective career evaluations.

The Career Satisfaction Scale: Longitudinal Measurement Invariance and Latent Growth Analysis. - Spurk, Daniel; Abele, Andrea E.; Volmer, Judith (Journal of Occupational and Organizational Psychology, 2011)
The present research analyses the adequacy of the widely used Career Satisfaction Scale (CSS; Greenhaus, Parasuraman, & Wormley, 1990) for measuring change over time. We used data of a sample of 1,273 professionals over a 5-year time period. First, we tested longitudinal measurement invariance of the CSS. Second, we analysed changes in career satisfaction by means of multiple indicator latent growth modelling (MLGM). Results revealed that the CSS can be reliably used in mean change analyses. Altogether, career satisfaction was relatively stable over time; however, we found significant variance in intra-individual growth trajectories and a negative correlation between the initial level of and changes in career satisfaction. Professionals who were initially highly satisfied became less satisfied over time. Theoretical and practical implications with respect to the construct of career satisfaction and its development over time (i.e., alpha, beta, and gamma change) are discussed. (PsycINFO Database Record (c) 2014 APA, all rights reserved)
Keywords: Career Satisfaction Scale; test validity; test reliability; psychometrics; longitudinal measurement invariance; latent growth analysis

The construct of career success: Measurement issues and an empirical example. - Abele, Andrea E.; Spurk, Daniel; Volmer, Judith (Journal for labour market research, 2011)
The aim of the present paper is twofold. We first give an overview of the multi-faceted construct of career success with its “objective” (real attainments) and “sub- jective” (perceived attainments) components and with the different methodologies measuring them (“subjectivist” vs. “objectivist” approaches). We also discuss the relationship between the different components of career success as revealed in the literature. Our second aim is to show that the interrelationship between the different facets of career success varies with the emplo yment context. We analyze subjective and objective career success measures collected from professionals working either in the private sector, in the public sector, or that are self-employed. Our findings show that objective success and subjective success are more closely related in the private and self-employment sectors than in the public sector. Moreover, the interrelationship between objective and subjective success varies with the specific subjective success measure chosen. It is stronger for an “other-referent” subj ective success measure than for a “self-referent” subjective s uccess measure. Conclusions regarding the measurement of career success as well as regarding the relevance of subjective success for studying occupational careers are drawn
Keywords: Objective vs. subjective career success; Self-referent vs. other-re ferent subjective success; Interplay between objectiv e and subjective success in different fields of employment

The dual impact of gender and the influence of timing of parenthood on men’s and women’s career development: Longitudinal findings. - Abele, Andrea E.; Spurk, Daniel (International journal of behavioral development, 2011)
This study investigated the impact of gender, the gender-related self-concept (agency and communion), and the timing of parenthood on objective career success of 1,015 highly educated professionals. Hypotheses derived from a dual-impact model of gender and career-related processes were tested in a 5-wave longitudinal study over a time span of 10 years starting with participants’ career entry. In line with our hypotheses we found that the communal component of the gender self-concept had an impact on parenthood, and the agentic component influenced work hours and objective career success (salary, status) of both women and men. Parenthood had a negative direct influence on women’s work hours and a negative indirect influence on women’s objective career success. Women who had their first child around career entry were relatively least successful over the observation period. Men’s career success was independent of parenthood. Sixty-five percent of variance in women’s career success and 33% of variance in men’s career success was explained by the factors analyzed here. Mothers with partners working full time reduced their work hours more than mothers with partners not working full time. A test for a possible reverse influence of career success on the decision to become a parent revealed no effect for men and equivocal effects for women. We conclude that the transition to parenthood still is a crucial factor for women’s career development both from an external gender perspective (expectations, gender roles) and from an internal perspective (gender-related self-concept). (PsycINFO Database Record (c) 2012 APA, all rights reserved)
Keywords: gender differences; gender related self concept; agency; communion; timing of parenthood; career development; career success; working hours

The longitudinal impact of self-efficacy and career goals on objective and subjective career success. - Abele, Andrea E.; Spurk, Daniel (Journal of Vocational Behavior, 2009)
The present research reports on the impact of occupational self-efficacy and of career-advancement goals on objective (salary, status) and subjective (career satisfaction) career attainments. Seven hundred and thirty four highly educated and full-time employed professionals answered questionnaires immediately after graduation, three years later, and seven years later. Controlling for discipline, GPA at master's level, and gender, we found that occupational self-efficacy measured at career entry had a positive impact on salary and status three years later and a positive impact on salary change and career satisfaction seven years later. Career-advancement goals at career entry had a positive impact on salary and status after three years and a positive impact on status change after seven years, but a negative impact on career satisfaction after seven years. Women earned less than men, but did not differ from men in hierarchical status and in career satisfaction. Theoretical implications for socio-cognitive theorizing and for career-success research as well as applied implications for vocational behavior are discussed. (PsycINFO Database Record (c) 2014 APA, all rights reserved)
Keywords: self-efficacy; career goals; career success; employed professionals

Validation of the German Career Decision-Making Profile–An Updated 12-Factor Version - Ebner, Katharina; Thiele, Lisa; Spurk, Daniel; Kauffeld, Simone (Journal of Career Assessment, 2016)

What makes us more employable and successful? Career sponsorship within early academic science careers through networking and career coaching interventions - Spurk, Daniel; Kauffeld, Simone; Ebner, Katharina; Volmer, Judith (International Conference for Well-Being and Performance, 2014)

Who earns more and why? A multiple mediation model from personality to salary. - Spurk, Daniel; Abele, Andrea E. (Journal of Business and Psychology, 2011)
Purpose: The purpose of this study was to investigate multiple indirect Big Five personality influences on professionals’ annual salary while considering relevant mediators. These are the motivational variables of occupational self-efficacy and career-advancement goals, and the work status variable of contractual work hours. The motivational and work status variables were conceptualized as serial mediators (Big Five → occupational self-efficacy/career-advancement goals → contractual work hours → annual salary). Design/Methodology/Approach: We realized a 4 year longitudinal survey study with 432 participants and three points of measurement. We assessed personality prior to the mediators and the mediators prior to annual salary. Findings: Results showed that except for openness the other Big Five personality traits exerted indirect influences on annual salary. Career-advancement goals mediated influences of conscientiousness (+), extraversion (+), and agreeableness (-). Occupational self-efficacy mediated influences of neuroticism (–) and conscientiousness (+). Because the influence of occupational self-efficacy on annual salary was fully mediated by contractual work hours, indirect personality influences via occupational self-efficacy always included contractual work hours in a serial mediation. Implications: These findings underline the importance of distal personality traits for career success. They give further insights into direct and indirect relationships between personality, goal content, self-efficacy beliefs, and an individual’s career progress. Originality/Value: Previous research predominantly investigated direct Big Five influences on salary, and it analyzed cross-sectional data. This study is one of the first to investigate multiple indirect Big Five influences on salary in a longitudinal design. The findings support process-oriented theories of personality influences on career outcomes. (PsycINFO Database Record (c) 2012 APA, all rights reserved)
Keywords: personality; salaries; Big Five personality Model; mediation models; motivation; occupational self efficacy; career advancement goals; work hours

Why are proactive people more successful in their careers? The role of career adaptability in explaining multiple career success criteria - Spurk, Daniel; Volmer, Judith; Hagmaier-Göttle, Tamara; Kauffeld, Simone (Personality traits : causes, conceptions and consequence, 2013)
Analyzed the contemporary career variable of career adaptability as the underlying mechanism in the proactive personality-career success relationship, and aimed to broaden the criteria of career success to the era of the boundaryless career (i.e., internal and external marketability). The analyzed sample was comprised of 153 participants from organizations in the fields of software and IT as well as the textile and automotive industry. Participants completed questionnaires assessing proactive personality, career adaptability, and subjective career success (career satisfaction, job satisfaction, and internal and external marketability). Objective career success was operationalized as salary, bonuses, and promotions. Bivariate and path analytical results showed that career adaptability acts as an important underlying mechanism for the relationship of proactive personality and several career success criteria (except bonuses). Results are discussed with respect to proactive personality research, new career research, and career success research.
Keywords: Persönlichkeitsmerkmale; Anpassungsfähigkeit (Persönlichkeit); Beruflicher Erfolg; Berufliche Entwicklung; Arbeitszufriedenheit; Arbeitstauglichkeit; Löhne und Gehälter; Beförderung (berufliche Karriere)

Why Do Adaptable People Feel Less Insecure? Indirect Effects of Career Adaptability on Job and Career Insecurity via Two Types of Perceived Marketability - Spurk, Daniel; Kauffeld, Simone; Meinecke, M.; Ebner, Katharina (Journal of Career Assessment, 2015)